Monte Carlo method for predicting of cardiac toxicity: hERG blocker compounds. (27th May 2016) - Gobbi, Marco; Beeg, Marten; Toropova, Mariya A.; Toropov, Andrey A.; Salmona, Mario
Graphical abstract: Highlights: Predictive models for cardiac toxicity are built up. The models are calculated with the Monte Carlo method. The CORAL software is utilized to build up the models. The statistical quality of the models is quite good. The models are built up in accordance with the OECD principles. Abstract: The estimation of the cardiotoxicity of compounds is an important task for the drug discovery as well as for the risk assessment in ecological aspect. The experimental estimation of the above endpoint is complex and expensive. Hence, the theoretical computational methods are very attractive alternative of the direct experiment. A model for cardiac toxicity of 400 hERG blocker compounds ( pIC50 ) is built up using the Monte Carlo method. Three different splits into the visible training set (in fact, the training set plus the calibration set) and invisible validation sets examined. The predictive potential is very good for all examined splits. The statistical characteristics for the external validation set are (i) the coefficient of determination r 2 = (0.90-0.93); and (ii) root-mean squared error s = (0.30–0.40).